Differences in Nordic Hamstring Exercise and Contract Relax Stretching on Increasing Flexibility in Students with Hamstring Tightness at Muhammadiyah University of Sidoarjo: Perbedaan Nordic Hamstring Exercise dan Contract Relax Stretching Terhadap Peningkatan Fleksibilitas pada Mahasiswa dengan Hamstring Tightness di Universitas Muhammadiyah Sidoarjo - Putri, Lidya Shafika; Anjasmara, Bagas; Widanti, Herista Novia (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the differences between Nordic Hamstring Exercise and Contract Relax Stretching on increasing flexibility in students with Hamstring Tightness at Muhammadiyah University of Sidoarjo, with male and female respondents aged 19-24 years experiencing hamstring tightness. Methods: This study was conducted by comparing the increased flexibility of the group given Nordic Hamstring Exercise with the Contract Relax Stretching group, hamstring flexibility was measured by measuring the hip joint range of motion during the passive straight leg raise (SLR) or active knee extension (AKE) test. Results: The results of this study were paired sample T-test in both groups, where in group 1 the mean value of the pre-test was changed from 42.69±6.957 to 20.77±7.316 at the time of post-test, p value = 0.001 ( p<0.05). Meanwhile, in group 2, the mean value of the pre-test was changed from 43.85±10.637 to 32.31±0.919 at the post-test, the value of p=0.001 (p<0.05) it can be concluded that there is a change in the flexibility of the hamstring muscles in students after being given Nordic Hamstring Exercise and Contract Relax Stretching. The results of the Independent T-test showed a p value = 0.004 <0.05, which means that there are differences in the effectiveness of the two groups to increase the flexibility of the hamstring muscles in students.